A Rare Disease of Familial Chylomicronemia Syndrome in a 20 Days Infant (Journal of Armed Forces Medical College, Bangladesh, 2020)
Familial chylomicronemia syndrome is a group of very rare genetic disorders. It is inherited as autosomal recessive disorder. Its estimated incidence is 1 in 1000000 populations, characterized by deficient activity of an enzyme lipoprotein lipase (LPL) or apo-protein C-II, resulting into severe fasting hypertriglyceridemia and massive accumulations of chylomicrons in plasma. LPL deficiency typically presents in childhood with failure to thrive, colicky abdominal pain, eruptive xanthomas, lipemiaretinalis, pancreatitis and hepatomegaly. We are reporting a rare case of familial chylomicronemia in a 20 days old child who was presented with pneumonia, his plasma incidentally found like milk during routine collection of his blood sample. As the child was only 20 days old with very high triglyceride level, so breast feeding continued and cocktail therapy with low dose Tablet Fenofibrate, Tablet Niacin, Tablet Atovastatin started after referral to paediatric cardiologist at 3 months of age.Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 107-109